Association of Veggie Meter–Assessed Skin Carotenoids and Dietary Intake Among Indigenous Families: The Indigenous Supported Agriculture “Go Healthy” Study - Susan B Sisson; Emma Kasahara; Shanon Casperson; Stephanie Jilcott Pitts; Jessica Reese; Ying Zhang; Tori Taniguchi; Kaylee R Clyma; Jann Hayman; Valarie Blue Bird Jernigan (Current Developments in Nutrition)
Background: Indigenous communities have seldom been included in previous research on skin carotenoid scores (SCS) and diet. Further, little is known about familial SCS. Objectives: This study aimed to examine associations between SCS and body mass index (BMI), dietary intake among adults and children in Osage Nation, and examine associations between SCS among family members. Methods: This cross-sectional study examined SCS measured using a Veggie Meter. Adults completed a single 24-h diet recall to calculate the Healthy Eating Index (HEI)-2015. Linear mixed modeling was used to examine associations, while accounting for family correlation. Linear regression (adjusting for age, sex, BMI, tobacco use, and season) was used to examine associations between SCS and diet. Spearman correlation were used to examine associations between SCS between household members. Results: Among the study population, 61% of adults (n = 445) was females and 93% overweight/obese; HEI was 42.7 ± 11.2; and SCS was 211.8 ± 57.9. Further, 55.6% of children (n = 135, 3–17 y) was females and 45.2% overweight/obese, with HEI of 207.8 ± 62.0. In adults, SCS were higher in males than that in females (226.0 ± 61.0 compared with 203.6 ± 55.1; P < 0.001). Children <10 y had higher SCS than those ≥10 y (221.4 ± 65.8 compared with 194.2 ± 55.5; P = 0.017). Children with obesity (178.4 ± 44.0) had significantly lower SCS than children in other weight classifications (P = 0.023). HEI was significantly associated with SCS (β: 0.50; 95% CI: 0.01, 0.99). Household adult SCS was significantly correlated (r = 0.26; P = 0.005). SCS among children <10 y were significantly associated with adult SCS (r = 0.34; P = 0.037). No correlations were observed in SCSs between children ≥10 y and adults. Conclusions: Adult males, younger (<10 y) children, and nonobese children show higher SCS. A healthier overall diet, as measured by HEI, is associated with higher SCS in adults, while controlling for covariates. Within families, SCS between adults were correlated, indicating similar dietary intake of fruit and vegetables. Adult SCS within households is associated with young children’s (<10 y) SCS, but not with that of older children (≥10 y).